Effect of striped catfish (Pangasianodon hypophthalmus) for cartilage thickness and chondrocyte count in mice (Mus musculus) - Akbar, Izaak Zoelkarnain; Oktaviyanti, Ika Kustiyah; Rasyid, Sukma Ihsan; Wibowo, Agung Ary; Putera, Husna Dharma; Utomo, Tjahyo Kelono; Sikumbang, Kenanga Marwan (Edelweiss Applied Science and Technology, 2025)
Osteoarthritis (OA) is a leading cause of disability worldwide, characterized by progressive cartilage degeneration. Nutritional interventions, particularly omega-3 polyunsaturated fatty acids (PUFAs), have shown potential in slowing cartilage degradation. Striped catfish (Pangasianodon hypophthalmus) is a rich source of omega-3 PUFAs and essential amino acids, which may support cartilage health and regeneration. A post-test-only control group design was implemented using 50 male mice (Mus musculus), randomly assigned to either a control group (standard diet) or a treatment group (striped catfish-supplemented diet). The intervention lasted for eight weeks. Cartilage thickness and chondrocyte count were measured histologically using ImageJ software, and statistical significance was determined using independent t-tests and Mann-Whitney U tests. The treatment group exhibited significantly increased cartilage thickness (p < 0.001) and chondrocyte count (p < 0.001) compared to controls. These findings suggest that the nutrients in striped catfish enhance cartilage metabolism, reduce inflammation, and support extracellular matrix (ECM) integrity. Striped catfish supplementation demonstrates significant benefits for cartilage health, potentially aiding in OA management. Future research should explore optimal dosages and long-term effects to further validate these findings.